Show that (sec(x))^2 /(sec(x)+1)(sec(x)-1) can be written as (cosec(x))^2.

( sec2(x))/((sec(x)+1)(sec(x)-1))Then, by the rule of 'difference of two squares', we know that this equals= (sec2(x))/(sec2(x)-1)= (sec2x/tan2x)since 1+tan2(x)=sec2(x), we get sec2(x)-1=tan2(x). By multiplying throughout by cos2(x), we get(sec2x/tan2x)=1/sin2(x)=cosec2(x)as required.

Answered by Rishi S. Maths tutor

10085 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve 2^(3x-1) = 3


The gradient of the curve at point (x,y) is given by dy/dx = [7 sqrt(x^5)] -4. where x>0. Find the equation of the curve given that the curve passes through the point 1,3.


Solve the simultaneous equations y+4x+1 = 0 and y^2+5x^2+2x = 0


Three forces of magnitude 50N, PN, QN all act in a horizontal plane in equilibrium. The diagram shows the forces. DIAGRAM: QN = EAST, 50 = SOUTH, PN = 120 DEGREES ANTICLOCKWISE FROM QN a) Find P. b) Find Q.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences